Taming a heartbreaker - Jackson, Brenda (Brenda Streater) (Jackson, Brenda (Brenda Streater). Westmoreland legacy., 2024)
"Redford St. James is having too much fun to settle down with just one woman. Until a Westmoreland family wedding reunites him with Carmen Golan. He can't get Carmen--gorgeous, sweet and a hopeless romantic--out of his mind. Even though she's outright said he's husband material! Him! And she believes any heartbreaker can be tamed--by the right person. Well, it's his duty to set her straight"--